Left–Right Reversal Recurrently Evolved Regardless of Diaphanous-Related Formin Gene Duplication or Loss in Snails - Noda, Takeshi; Satoh, Noriyuki; Gittenberger, Edmund; Asami, Takahiro (Journal of molecular evolution, 2023)
Bilateria exhibit whole-body handedness in internal structure. This left–right polarity is evolutionarily conserved with virtually no reversed extant lineage, except in molluscan Gastropoda. Phylogenetically independent snail groups contain both clockwise-coiled (dextral) and counterclockwise-coiled (sinistral) taxa that are reversed from each other in bilateral handedness as well as in coiling direction. Within freshwater Hygrophila, Lymnaea with derived dextrality have diaphanous related formin ( diaph ) gene duplicates, while basal sinistral groups possess one diaph gene. In terrestrial Stylommatophora, dextral Bradybaena also have diaph duplicates. Defective maternal expression of one of those duplicates gives rise to sinistral hatchlings in Lymnaea and handedness-mixed broods in Bradybaena , through polarity change in spiral cleavage of embryos. These findings led to the hypothesis that diaph duplication was crucial for the evolution of dextrality by reversal. The present study discovered that diaph duplication independently occurred four times and its duplicate became lost twice in gastropods. The dextrality of Bradybaena represents the ancestral handedness conserved across gastropods, unlike the derived dextrality of Lymnaea . Sinistral lineages recurrently evolved by reversal regardless of whether diaph had been duplicated. Amongst the seven formin gene subfamilies, diaph has most thoroughly been conserved across eukaryotes of the 14 metazoan phyla and choanoflagellate. Severe embryonic mortalities resulting from insufficient expression of the duplicate in both of Bradybaena and Lymnaea also support that diaph duplicates bare general roles for cytoskeletal dynamics other than controlling spiralian handedness. Our study rules out the possibility that diaph duplication or loss played a primary role for reversal evolution.